Factors demotivating high school gifted students : - Trần, Hoàng Oanh (Can Tho University, 2016)
The purpose of the study is to investigate factors demotivating EFL classroom in the context of a specialized high school im Mekong Delta, to find out the differences of the demotivating factors among different grades as well as indicate the difference of demovating factors amont students majored in different subjects ....